Returns to Education: A Review of Classical Literature - IOAKIMIDIS, Marilou (Journal of Research in Educational Sciences; Vol 8 No 10 (2017): Volume VIII, Issue 10, 2017, 2018)
The aim of this paper is to navigate through the existing literature on Returns to Education and suggest new pathways for further research. For this purpose, a number of classical studies and papers were collected and analysed covering a time spectrum of approximately 40 years (1964-2007). Drawing from North American as well as international literature in the field this paper sheds light on the economic effects of education from various angles, including returns related to educational attainment, field of study, gender, sector of employment and quality of educational institutions. In addition, this work attempts to unveil historical patterns in returns to education diachronically. Finally this paper examines the literature of the above-mentioned aspects for Greece.